Improving Students' Interest by Using Matching Card Media - Sonya Damayanthi; Maulidhan Agyansyah (IKIP Siliwangi, 2018)
There are so many words in English. Learning these words is a big problem for students of English. However, there are ways to solve this problem. One way is to become familiar with the process of word formation. This process enables students to understand how a word is formed. This analysisis in important and use ful to learn because they are very commonly used in English. Developing some skills in taking words apart will help students better understand what they read, what the meaning of a word, and finally increase students' interest. The purposes of this research are to find out wheter using matching card media can improve students interest in learning english and what the students responses. The subject of this research was class XI Slb ; which consisted of 8 students. This research was done in two cycles. The researcher used short answer tests, observation checklist tables, and field notes as the tools of collecting data. The research finding showed that the students interest to learning english language improved the first cycle to the last cycle. The result of the students 70 % improved their interest , improved their in speaking 40%, improved student writing 70%, recognize word formation and matching card process 70%, participate in class discussion 25%, and get better class attendance. From the result above, the-writers believe that matcing card is very use ful to improve students' intererst and has positive impact towards the students learning process.